The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1002/(sici)1097-4571(199201)43:1<72::aid-asi7>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The size of retrieval sets

Abstract: This study was concerned with the question of how much information users of online search services want when they have a search conducted. This question was investigated within the context of multiattribute decision making. Thirty-two individuals rated their likely satisfaction with the results of hypothetical online searches on a Pl-point scale. The hypothetical searches varied in terms of the number of documents retrieved, the percentage of retrieved documents that were relevant to the searcher's topic (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, Harter (1992, p. 608) indicates that if the user is using a “psychological” rather than purely “topical” criterion of relevance, a citation that “topically” matches the user's topic, but contains information the user has previously processed, may be passed over by the user because it is not “new” (cf. also, Kinnucan, 1992; Korfhage, 1997; Park, 1994; cf. Tiamiyu & Ajiferuke, 1988, for the related issue of interaction effects in judging citation lists).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Harter (1992, p. 608) indicates that if the user is using a “psychological” rather than purely “topical” criterion of relevance, a citation that “topically” matches the user's topic, but contains information the user has previously processed, may be passed over by the user because it is not “new” (cf. also, Kinnucan, 1992; Korfhage, 1997; Park, 1994; cf. Tiamiyu & Ajiferuke, 1988, for the related issue of interaction effects in judging citation lists).…”
Section: Introductionmentioning
confidence: 99%
“…Concerns with the size of retrieval sets led to the investigation of whether the size of retrieval sets affects relevance judgement [57]. The findings from Kinnucan's study indicated that the size of retrieval sets affects relevance judgement in a complex way.…”
Section: The Evaluating Interaction Processmentioning
confidence: 99%
“…As for how many records are wanted, a 30-record response is widely considered a typical optimal result, and professional searchers view 50 to 70 references as optimal (Bates, 1986;Wiberly & Dougherty, 1988). Kinnucan (1992) found satisfaction relatively una ected by retrieval set size but sensitive to precision, though less so as retrieved set size increased.…”
Section: What Do Library Users Want?mentioning
confidence: 99%